Bioactivity and osteointegration of hydroxyapatite-coated stainless steel and titanium wires used for intramedullary osteosynthesis; Strategies in Trauma and Limb Reconstruction; Vol. 12, iss. 2 - Popkov A. V. Arnold Vasiljevich; Gorbach E. N. Elena Nikolaevna; Kononovich N. A. Nataljya Andreevna; Popkov D. A. Dmitry Arnoldovich; Tverdokhlebov S. I. Sergei Ivanovich; Shesterikov E. V. Evgeny Viktorovich (2017, 2017)
Title screen